2016
DOI: 10.1371/journal.pone.0163658
|View full text |Cite
|
Sign up to set email alerts
|

A Gram Stain Hands-On Workshop Enhances First Year Medical Students' Technique Competency in Comprehension and Memorization

Abstract: BackgroundLaboratory diagnostic tests have an essential role in patient care, and the increasing number of medical and health professions schools focusing on teaching laboratory medicine to pre-clinical students reflects this importance. However, data validating the pedagogical methods that best influence students’ comprehension and interpretation of diagnostic tests have not been well described. The Gram stain is a simple yet significant and frequently used diagnostic test in the clinical setting that helps c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…According to the results of Gram staining, bacteria can be classified into 2 categories: Gram‐positive G+ and Gram‐negative G(Delfiner, Martinez, & Pavia, ). Hospital‐acquired infections caused by antibiotic‐resistant Gram‐negative bacteria (GNB) are increasingly seen (Ivády et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of Gram staining, bacteria can be classified into 2 categories: Gram‐positive G+ and Gram‐negative G(Delfiner, Martinez, & Pavia, ). Hospital‐acquired infections caused by antibiotic‐resistant Gram‐negative bacteria (GNB) are increasingly seen (Ivády et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The competency for microscopic examinations can be enhanced through lectures, group discussions, and hands‐on workshops. Among them, hands‐on workshops showed the highest education effect 21 . Our study also indicated that the experience acquired by performing microscopic examinations contributed to improving its sensitivity.…”
Section: Discussionmentioning
confidence: 54%
“…Among them, hands-on workshops showed the highest education effect. 21 Our study also indicated that the experience acquired by performing microscopic examinations contributed to improving its sensitivity. Besides, an appropriate feedback increases the efficacy of the educational process.…”
Section: Ta B L Ementioning
confidence: 58%
“…Although there are facilities with established feedback systems for PCGS in other research, there is no standardized educational program for PCGS in Japanese teaching hospitals [ 10 ]. However, it is reported that practical hands-on training, including workshops, can improve the accuracy of Gram stain interpretation [ 24 ]. Therefore, the educational progress of Gram stains, along with recognizing prevalent diagnostic errors and characteristics, could make PCGS a reliable diagnostic tool even for obstructive pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%